A self-sorted gel network formed by heating a mixture of soy and cod proteins. Issue 8 (1st August 2019) - Wu, Chao; Yan, Xinyu; Wang, Tao; Ma, Wuchao; Xu, Xianbing; Du, Ming
Abstract : A self-sorted gel network was formed by heating a binary system of cod and soy proteins. Abstract : The development of binary protein networks featuring superior nutritional and rheological properties is an intriguing, as well as challenging, aspect in the food industry. In this study, a novel, self-assorted double protein network was constructed, which was achieved by simply heating soy protein (SP) and cod protein (CP) at 100 °C with different SP/CP ratios (5 : 0 to 0 : 5). Atomic force microscopy revealed that the heat-induced protein aggregate size increased with increasing CP ratio from 0 to 100%, which was accompanied by a significant increase in surface hydrophobicity and the content of disulfide bonds. Meanwhile, the ratio of non-network proteins in the gel network decreased significantly from 12.5 to 3.2% with the increase of the CP ratio from 0 to 100%. Concomitantly, the networks formed at a higher CP ratio were found to be less homogeneous and more porous with higher storage modulus. Interestingly, results from far-UV CD, near-UV CD, and fluorescence demonstrated that there were no interactions between SP and CP during thermal treatment, suggesting that the gel formed by mixed proteins was a self-sorted network. The study would advance the utilization of blended fish proteins and plant proteins toward tailor-made double networks that may find many applications in food and relevant areas.